Nursing Intervention in Handling Covid-19 Hypoxia Patients in the Isolation Room of Covid-19 Hospital Badaruddin Kasim Tanjung South Kalimantan - Mohammad Basit Basit; Irwani Sunardi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
Coronavirus 2019 (Covid-19) is an infectious disease caused by the acute respiratory syndrome of coronavirus 2 (Sars-CoV-2). Some complaints appear in patients who are confirmed to be covid-19, one of which is hypoxia, hypoxia is a condition of low levels of O2 contained in cells / tissues to below the physiological level. Nursing intervention activities against clients with hypoxia that nurses must do is to adjust the position of the client's body to reduce lung workload, teach correct breathing techniques, pay attention to the environment, collaboration on O2 administration. The research aims to find out nursing interventions in handling Covid-19 hypoxia patients in the Covid-19 Isolation Room of H. Badaruddin Kasim Tanjung Hospital. This study used qualitative methods with interview techniques that explained the implementation of nursing interventions with hypoxia clients with COVID-19 in the Isolation Room of Badaruddin Kasim Tanjung Hospital. Sampling using purposive sampling techniques. Data is analyzed through the results of interview recordings in the form of verbatim transcripts or descriptions of recordings in the form of written descriptions or narative texts. based on the results of the interview produced 6 sub themes, namely changing the position of semifowler patients in maximizing breathing, oxygen administration, monitor respiration status, observation of the respiratory department, monitor symptoms of hypoxia & happy hypoxia, and airway monitor.